International law and the Arctic - Byers, Michael, 1966-; Baker, James (Arctic scholar); Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
Climate change and rising oil prices have thrust the Arctic to the top of the foreign policy agenda and raised difficult issues of sovereignty, security and environmental protection. Improved access for shipping and resource development is leading to new international rules on safety, pollution prevention and emergency response. Around the Arctic, maritime boundary disputes are being negotiated and resolved, and new international institutions, such as the Arctic Council, are mediating deep-rooted tensions between Russia and NATO and between nation states and indigenous peoples. International Law and the Arctic explains these developments and reveals a strong trend towards international cooperation and law-making. It thus contradicts the widespread misconception that the Arctic is an unregulated zone of potential conflict.
1. Territory -- 2. Maritime boundaries -- 3. Beaufort Sea boundary -- 4. Extended continental shelves -- 5. Arctic straits -- 6. Environmental protection -- 7. Indigenous peoples -- 8. Security.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Marine resources conservation -- Law and legislation; Arctic regions -- International status; Arctic regions -- International cooperation; Barents Sea -- International status; Beaufort Sea -- International status; Electronic books